Modulation of the IGF system and proliferation in human endometrial stromal cells by metformin: a dose-dependent effect - Jung, Marie-Luise; Jauckus, Julia; Zorn, Markus; Capp, Edison; Strowitzki, Thomas; Germeyer, Ariane (Archives of gynecology and obstetrics, 2015)
PurposeTo assess the metformin effect on endometrial stromal cell decidualization, proliferation, gene and protein expression of IGFBPs, IGFs and their receptors.MethodsHuman endometrial stromal cells (hESCs) were cultured from endometrial biopsies of 11 women undergoing surgery for benign reasons. hESCs were decidualized with and without metformin in increasing doses. Supernatant and cells were harvested after decidualization for 12-14 days, followed by real-time PCR of IGFBP 1-6, IGF I, IGF II and their receptors. Prolactin, and IGFBP-1, -3, and -6 were additionally analyzed in supernatant by ELISA. Proliferation of hESCs and decidualization of hESCs were assessed under the influence of metformin. Data were analyzed using the paired t test with p < 0.05 considered significant.ResultsWhile lower concentrations of metformin (10−4, 10−5 M) did not influence the decidualization and proliferation capacity of hESCs, higher concentrations (10−3, 10−2 M metformin) significantly (p < 0.05) diminished decidualization, as well as stromal cell proliferation in a dose-dependent manner. Higher concentrations of metformin lead to a significant (p < 0.05) dose-dependent attenuation of the progesterone effect with regard to IGFBP-1, -3, -5, -6, as well as IGF I receptor, while it did not change the expression of IGFBP-2 and -4, IGF I and II and the IGF II receptor. This was confirmed on the protein level for IGFBP-1, -3, and -6.ConclusionWe were able to demonstrate for the first time a dose-dependent local effect of metformin within hESCs. Metformin might therefore influence locally the endometrial proliferation and maturation, and could open up new treatment options for gynecological diseases by vaginal application of metformin.
Gesehen am 22.02.2017